Study on Smart Home Interface Design Characteristics Considering the Influence of Age Difference: Focusing on Sliders - Yu, Na; Ouyang, Ziwei; Wang, Hehe (Frontiers in Psychology, 2022)
Smart homes represent an effective approach to improve one’s quality of life. Developing user interfaces that are both comfortable and understandable can assist users, particularly the elderly, embrace smart home technologies. It’s critical to concentrate on the characteristics of smart home interface design and their impact on people of various ages. Since sliders are one of the most common components utilized in the smart home user interface, this article aimed to investigate the effects of slider design characteristics (e.g., button size, track color, and sliding orientation) on user performance and preference. Thirty-four participants were recruited for the experiment (16 for the young group, aged between 18 and 44 years; 18 for the middle-aged and elderly group, aged between 45 years and above). Our results revealed that both groups had shorter task completion time, less fixation time, and saccades on horizontal sliding orientation and larger buttons, which means better user performance. For the older group, the slider with color gradient track led to better user performance, while the track color only had less effect on the performance of the younger group. In terms of user preference, the results and performance of the older group were basically consistent, while the younger group had no significant difference in sliding orientation and track color.